Role of Religiousness/Spirituality in Resilience of Fisheries College Cadets - Rahmawati, Sri (Universitas Ahmad Dahlan, 2014)
AbstractÂ Experts agree that resilience involves internal factors and external factors. In addition to those two factors, religious beliefs, spirituality and the capacity to give a meaning to the traumatic event, it is also discussed as a factor involved in the development of resilience. A number of researchers explore their findings to see the relationships between religiousness/ spirituality and resilience. People experiencing emptiness of spiritual, increasingly awareness of the importance of the involvement of religion/spiritual in solving problems, but itâs increasingly depletion due to exposure to materialistic life.This researchÂ is conducted to see the influence of religiousness/spirituality on resilience occuring among college students. The results showed that the following dimensions are related to the increasing resilience of a person: daily experience of human spiritual, beliefs/values, willingness to forgive, and the worship of religious activities as well as evaluating a persons level of religiousness. Discussion and implication of the research results are included.Â Keyword: Religious coping; Resilience; Cadets of STP; Quantitative ResearchÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â